Pendidikan Karakter dalam Perspektif Tasawuf: Studi Konseptual Atas Pemikiran Al-Junaid Al-Baghdadi - Hafiz Hafiz; Muhammad Afdal (Jurnal Studi Pendidikan Agama Islam, 2025)
This study is motivated by the moral and ethical crisis affecting the younger generation due to the weakening of spiritually-based character education. The article aims to formulate a modern character education model grounded in Sufi teachings, particularly the thought of Imam Al-Junaid Al-Baghdadi, as a solution to moral degradation. The scope covers character education concepts from a Sufi perspective, foundational values underlying character formation, and their implementation in contemporary education. The method employed is a conceptual study with a textual and critical approach to Al-Junaid’s works and literature on Sufism and character education. Findings reveal that character education according to Al-Junaid emphasizes heart purification, controlling base desires, and instilling tauhid as the main foundation. The implementation of values such as patience, sincerity, contentment, and asceticism can shape morally upright individuals with spiritual-social balance, relevant to overcoming modern educational challenges. This model offers a holistic alternative for shaping today’s generation's character.